EXPRESSION OF THE CONCEPT OF "FOOD" IN ENGLISH AND UZBEKISTAN - I. K. Ablakulova,Daminova Sevinch Zokirjon kizi (International Journal of Literature and Language Studies, 2026)
This article comparatively analyzes the linguocultural and semantic features of the concept of “food” in English and Uzbek languages. The study focuses on the expression of the concept of food in proverbs, idioms, metaphors, and phraseological units. In addition, the national culture, mentality, and values of the English and Uzbek peoples are revealed through food-related linguistic expressions. The analysis identifies both similarities and differences in the representation of the concept of food in the two languages and highlights the close relationship between language and culture.